Banks’ Performance in Thailand: Profitability and Efficiency, 2009-2013 - Arsayawachira, Pariyada (2016)
The purpose of this study is to examine the cost efficiency as well as investigate the influence of bank-specific, industry-specific and macroeconomic variables on banks’ profitability. The panel data of twenty commercial banks in Thailand during 2009-2013 is adopted to estimate the cost efficiency by employing SFA technique as well as to investigate the profitability by applying GMM approach. The empirical results illustrate that commercial banks in Thailand maintain the high level of average cost efficiency around 76.22-94.29%. There are four determinants significantly affect banks’ profitability. ROEt-1 and GDP have the positive relationship whilst SMD and Z-score have the negative association with the profitability. This research provides several benefits for commercial banks, policymakers, regulators and the government to develop the appropriate strategy and regulatory policy. Furthermore, it is advantageous for the further study of other literatures.